The Effect of Financial Support, Creativity, and Regulatory Environment on the Growth of MSMEs - Bekti Utomo (International Journal of Integrative Sciences, 2024)
This study looks at the financial assistance, innovation, and regulatory environment as key determinants of the growth of Micro, Small, and Medium-Sized Enterprises (MSMEs) in the West Javan cities of Depok and Bogor. A structured questionnaire survey was used to gather data from MSME owners and operators using a quantitative research approach. The data was analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The findings show a strong correlation between financial assistance, innovation, the business climate, and MSME expansion. Increased MSME growth is linked to better financial support, innovative ideas, and a supportive regulatory framework. These results highlight the significance of addressing a variety of issues in order to promote the expansion of MSMEs and offer insightful information to stakeholders, policymakers, and company owners who wish to assist in the growth of the MSME sector in the area.